Development of prediction equation for methane‐related traits in beef cattle under high concentrate diets. (16th January 2020) - Uemoto, Yoshinobu; Ogawa, Shinichiro; Satoh, Masahiro; Abe, Hiroyuki; Terada, Fuminori
Abstract: The objective of this study was to develop a prediction equation for methane‐related traits in beef cattle and evaluate this equation using datasets with different cattle breeds and roughage rates. Enteric methane emission (CH4, l/day) was measured using open‐circuit respiration chambers. Dry matter intake (DMI, kg/day), body weight (BW, kg), daily gain (DG, kg), total digestible nutrients (TDN, %DMI), and roughage rate (Rrate, %) were used as independent variables, and methane‐related traits—CH4, CH4 per DMI (CH4 /DMI, l/kg), and methane conversion factor (MCF, %)—were used as dependent variables. The best‐fit equations to predict methane‐related traits using a total of 76 records were CH4  = –676.7 + 0.04194 × BW + 29.88 × DMI + 7.883 × TDN + 4.367 × Rrate, CH4 /DMI = –52.24 – 1.193 × 10 –3  × BW – 5.905 × DG + 1.077 × TDN + 0.5008 × Rrate, and MCF = –11.43 – 5.308 × 10 –4  × BW – 1.223 × DG + 0.2336 × TDN + 0.1157 × Rrate. The predictive ability of the developed equations differed between roughage rates but not between breeds. For CH4, the predictive ability of the developed equations was better compared with previously reported equations in the low roughage rate dataset, but not in the high roughage rate dataset. Our results suggest that the developed equations of methane‐related traits can be applied in beef cattle fed with low roughage diets.